Genotypic resistance profiles of HIV-2 infected patients from Cape Verde failing first-line antiretroviral therapy - Moranguinho, Inês (2019)
The pol gene from HIV-2 infected patients from Cape Verde experiencing virologic failure was sequenced and drug resistance mutations were determined. Most patients were taking a first line regimen of AZT, 3TC and LPV/r. Resistance mutations were found in most patients (11/17, 64.7%) especially I82F (4/7, 57.1%) and M184 V (10/17, 58.8%). Resistance to all reverse transcriptase and protease inhibitors was found in 58.8% (10/17) of the patients. Integrase inhibitors are warranted to treat these patients.